Analysis of an intense bora event in the Adriatic area. - D. Cesini; MORELLI, Sandra; F. Parmiggiani (2003)
Bora is a cold, strong, low level wind which blows mainly from NE along the Adriatic coast. However, bora-like winds occur in other regions i.e. Antarctic slope winds, Boulder windstorms. Cold air, forced through channels between higher terrain and accelerated by katabatic effects, can reach downslope very high speed, with strong spatial gradient and temporal variations. This wind affects coastal area and alters significantly the Adriatic sea status. Nowadays is still difficult to predict accurately its intensity, longevity and internal structure, which are related to mesoscale features as well as to local effects. Moreover, high resolution is needed. The meteorological Eta model is used to study the features of an intense real bora event recently occurred in the Adriatic area. Eta is a three-dimensional, primitive equation, hydrostatic, grid-point model. It is operational at the National Center for Environmental Prediction of the U.S. National Weather Service. ECMWF data are used to initialize model integration. Both single run and one-way nested run are performed. Model output is compared to ECMWF data, to composite sea surface temperature (SST) maps of northern Adriatic and to scatterometric measurements from QuikSCAT satellite. The daily SST maps are obtained by processing AVHRR data and by composing maps of 8-10 satellite passes in the day, in order to reduce cloud cover which affects their quality. QuikSCAT Level3 wind data are obtained from the PODAAC/JPL web site at the spatial resolution of 0.25 degrees, two times a day, in the morning (ascending) and in the afternoon (descending) satellite pass.